FACTORS AFFECT COMPANY VALUE IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - LINDA SANTIOSO; NURAINUN BANGUN; YUNIARWATI YUNIARWATI (Jurnal Bisnis dan Akuntansi, 2020)
The purpose of this research is to examine the effect of profitability, enterprise risk management and corporate social responsibility on firm value. The sample of this research limited to manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2015. This research uses 150 data with 50 companies selected per year. Analysis tool used multiple linear regression of SPSS 21.00. The dependent variable on this research is firm value, and the independent variable returns on equity, enterprise risk management, and corporate social responsibility. The result showed that return on equity and enterprise risk management affect the firm value, while corporate social responsibility has no effect on firm value.